Enhancing Efficiency in Outsourcing Workforce through Business Process Management for Digital Transformation - Barnabas Simorangkir (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The growing use of outsourced workforces in large organizations increases the need for effective governance, transparency, and process integration in outsourcing contract management. However, many organizations still rely on manual, fragmented, and non-standardized processes that lead to delays, data inconsistencies, and operational risks. This study aims to analyze and redesign outsourcing contract management processes using a business process management approach to support structured digital transformation. This research adopts a qualitative case study methodology, employing structured interviews with key stakeholders, direct observation, and internal document analysis. Six core processes were examined: man-power planning, recruitment and selection, onboarding, performance management, contract renewal, and exit management. existing processes were modeled using BPMN and analyzed through value-added analysis and RACI matrix to identify inefficiencies and role concentration. Based on the findings, a redesigned process model was developed, emphasizing process standardization, system integration, and phased digitalization. The results indicate that business process management-based digitalization can improve efficiency, accountability, and cross-unit coordination, supporting smart governance in outsourcing management within an emerging-market context.